Islamic microfinance as an alternative to conventional financing practices : The need to address the poverty in Pakistan - Abdul Razak, Dzuljastri; Abbas, Kausar (2012)
Microfinance has been identified as an important tool that can reduce poverty in developing countries. However, current practices are similar to conventional financing which are traditionally based on debt and price against interest rate. These practices do not effectively alleviate poverty as the micro entrepreneurs remain indebted throughout the period of financing. Hence, this paper explores the feasibility of Islamic microfinance as an alternative means to help the poor in line with the Shariah principles where the use of riba (usury) is prohibited due to unfairness and injustice. It begins with an overview of poverty, microfinance and its characteristics. This is followed by comparing the differences between conventional financing and Islamic microfinance and various models used. Then its application is discussed in the context of Pakistan. The study is an attempt to explore the emerging area of Islamic microfinance as a means to address the financial hardship facing micro entrepreneurs in order to improve their standard of living.